Design of ammonia sensor based on ZnO for analyzing hazards at critical infrastructure - Minska, Natalia; Bas, Oleh; Hvozd, Viktor; Hryhorenko, Oleksandr; Levterov, Alexander; Maliarov, Murat; Matiushenko, Mykola; Tarasov, Serhii; Chernysh, Roman; Shevchenko, Olga (Technology center PC, 2024)
A gas sensor based on ZnO has been designed, which demonstrates sensitivity to NH3 under standard conditions (temperature, 25 °С; pressure, 101.3 kPa). The experimental sample was manufactured by magnetron sputtering at direct current. A VUP-5M vacuum unit with an original material-saving magnetron was used to produce ZnO films. To analyze the efficiency of the gas sensor to ammonia (NH3) under standard conditions, its operating characteristics were studied. The concentration of NH3 for investigating operating characteristics was chosen at the level of 25 ppm. To determine the resistivity of the contacts of the instrument structure, the current-voltage characteristics of the gas sensor were examined in the voltage range between −100 and +100 V. Based on the results of investigating the current-voltage characteristics, which have a linear character, the resistivity of the contacts was confirmed. To study the sensitivity of the gas sensor to the target gas, the change in resistance of the sensitive layer of the gas sensor under the influence of NH3 with a concentration of 25 ppm under standard conditions was explored. The study results demonstrated the high sensitivity of the gas sensor to the target gas – at the level of 229 relative units. The investigation of the response and recovery time of the gas sensor showed that the ZnO-based gas sensor has a response and recovery time of 20 and 26 s, respectively. The selectivity of the ZnO-based gas sensor was studied. The selectivity study was carried out by determining the sensitivity of the gas sensor in the presence of vapors of various gases, namely methanol, ethanol, acetone. The study results showed that the reaction to ammonia is selective compared to the reaction to other gases. The results of examining the working characteristics of the ammonia gas sensor demonstrate the high efficiency of its application under standard conditions and a low concentration of the target gas.
Keywords: ZnO; gas sensor; magnetron sputtering; standard temperature; ammonia